Primeval history : Babylonian, biblical, and Enochic : an intertextual reading - Kvanvig, Helge S., 1948- (Supplements to the Journal for the study of Judaism, 2011)
The book offers a comprehensive analytic comparison between the images of primeval history in Babylonia, in the Hebrew Bible and the parallel Enochic traditions. It presents new interpretations of each of these traditions and how they relate to each other.